«The Black Hundreds». Activity of Monarchical Organizations in the Southern of Ukraine in the Years of the First Russian Revolution - Токаленко, Павло (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article deals with the activities of the right-monarchist organizations in the south of Ukraine during the First Russian Revolution of 1905-1907. Particular attention is paid to the role of the "Union of the Russian People" in organizing Jewish pogroms in the limited territory of residence of the Jewish people. The author draws attention to the full support and interest of the government of the Russian Empire in cooperation with the "black hundred" movement in the south of Ukraine. The division according to the chronology of the Jewish pogroms of the nineteenth and early twentieth centuries is aimed at confirming the assertion that the cooperation of power and monarchists has been strengthened in the struggle against the revolutionary moods in society at the beginning of the twentieth century. Statistics on Jewish pogroms in the south of Ukraine, point to the dynamic activity of monarchists, the peak of which falls on October 1905.